Illegal Disposal of Waste in Serbia – Current State and Penal Reaction - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Constant increase in the quantity of waste of various origins represents a global ecological issue. Developed countries, particularly the European Union member states, have been striving to improve their waste management systems for decades in order to facilitate, through the application of appropriate procedures and measures, the exploitation of waste as a useful resource and to ensure its safe and sustainable disposal. The countries passing through the phase of transition in the field of environmental protection are facing the problem of illegal waste disposal, which produces a negative impact on the environment as well as on the health of citizens living near illegal landfills of waste. Having in mind the efforts of the Republic of Serbia to harmonize its legislation and practice in the field of environmental protection with the European standards and to fulfill its international obligations under the Basel Convention, the author analyzes current state in the field of illegal waste disposal in Serbia, with focus on illegal landfills of waste, and legal mechanisms for the sanctioning of this phenomenon. After highlighting issues and obstacles, but also positive steps regarding waste disposal in Serbia, the author makes some suggestions for its improvement in accordance with the standards set in international sources of law.